2018
DOI: 10.1159/000492236
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Persistent Organic Pollutants and Anogenital Distance in Children at 18 Months

Abstract: Background: Anogenital distance (AGD) is a measure of in utero exposure to hormonally active agents. The aim of the present study was to evaluate the association between prenatal exposure to persistent organic pollutants (POPs) and AGD. Methods: POP levels were measured in pregnant women, and the AGD was recorded in 43 offspring at 18 months. We used linear regression models to analyze the association between maternal POP exposure and offspring AGD. We defined the anogenital index (AGI) as AGD divided by weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…First, our information on tobacco use during pregnancy was self-reported and may not be reliable; although we validated the information against urinary cotinine levels and observed a positive borderline statistically significant association between cotinine levels and AGI in female children. By contrast, no such association was observed in male children, but the regression coefficient was negative, suggesting that a shorter AGI may be the result of exposure to other endocrine-disrupting chemicals [ 28 , 34 , 35 , 36 ] and in contrast to what we observed when analyzing self-reported smoking variables. Moreover, maternal smoking status was recorded during the third trimester of pregnancy, which may have led to some misclassification of the exposure early in pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…First, our information on tobacco use during pregnancy was self-reported and may not be reliable; although we validated the information against urinary cotinine levels and observed a positive borderline statistically significant association between cotinine levels and AGI in female children. By contrast, no such association was observed in male children, but the regression coefficient was negative, suggesting that a shorter AGI may be the result of exposure to other endocrine-disrupting chemicals [ 28 , 34 , 35 , 36 ] and in contrast to what we observed when analyzing self-reported smoking variables. Moreover, maternal smoking status was recorded during the third trimester of pregnancy, which may have led to some misclassification of the exposure early in pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
“…AGD was measured according to methods described in detail elsewhere [ 59 ] and reported in our previous studies [ 34 , 35 ]. Vernier calipers were used to perform measurements in increments of 0.1 mm by two trained pediatricians.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…POPs are ubiquitous endocrine-disrupting compounds (EDC) that interfere with maternal hormones and can impact fetal development and health in later life. Studies have reported that maternal levels of POPs during pregnancy are associated with decrements in fetal growth and birth weight [ 5 9 ], neurodevelopmental disorders [ 10 ], earlier age of menarche [ 11 ], and genitourinary conditions in offspring [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anogenital index was inversely associated with lipid-adjusted concentrations of PBDE-99 and PBDE-153 but not with PCB congeners 13 . In a Danish mother-child cohort no consistent association between prenatal exposure to the pesticide metabolites 3-phenoxybenzoic acid (3-PBA), 3,5,6-trichloro-2-pyridinol (TCPY), 2,4-Dichlorophenoxyacetic acid (2,4-D) and dialkyl phosphates(DAPs) and AGD was found 14 .…”
Section: Organochlorine Compound Exposure and Agdmentioning
confidence: 84%